O Supremo Tribunal Federal numa democracia de direitos: a rejudicialização da corte e a repolitização da cidadania - Sousa, José Péricles Pereira de (2010)
This research, based on the observation that the Supreme Court (Supremo Tribunal Federal [STF]), in Brazil, is considered the last and principal interpreter of the Constitution, and analyzing this reality as a distortion that, largely, empties the meaning of the term popular sovereignty, seeks to reposition the notion of Constituent Power, showing it as translator of active citizenship and, thus, always ready to decide on key issues of political dynamic. To achieve this goal satisfactorily, there was literature and case law research, in a qualitative type, suggesting the review and development of concepts, following a phenomenological methodology, in the intention that this effort would be connect at current Brazilian spacetime, without write long introductory chapters and, in parallel, would be useful to a transformation of the research field verified. This attempt to re-reading of popular sovereignty took into account a paradigm of constitutional culture in which wish to participate and civic sense of social actors would demonstrate that the phenomenon of judicial activism is caused mainly by the apathy of citizens in building their own political destiny. The concept of democracy of rights referred to an ideal ambience of synergy between the three powers and the Constituent Power of the people, that would be expressed directly through referenda, plebiscites, popular consults and through the public sphere of discussion, enhanced by the possibilities of interaction of the new technologies (e.g., the internet). In another way, there were registered the difficulties in reaching this democratic instant, particularly because the gap of critical education and the uncertain world generated by waves of post-Modernity, supercapitalism and globalization. Nevertheless, it is believed that the institutional arrangement suggested in this essay readjust the functions of the Executive, Legislative, and especially, the Judiciary, so evident today, because would return to participation and to control the status of constitutionalism’s foundations, giving instruments to the society for the exercise of those functions.